Ecological reparation repair, remediation and resurgence in social and environmental conflict - Papadopoulos, Dimitris 1967-; Puig de la Bellacasa, María 1972-; Tacchetti, Maddalena (Dis-positions : troubling methods and theory in STS, 2023)
How do we engage with the threat of social and environmental degradation while creating and maintaining liveable and just worlds? Researchers from diverse backgrounds unpack this question through a series of original and committed contributions to this wide-ranging volume